Regenerative endodontic procedures: a review of the literature and a case report of an immature central incisor - Marc Llaquet; Montse Mercadé; Gianluca Plotino (Ariesdue, 2017)
Background: Trauma of developing teeth may lead to pulpal necrosis with subsequent arrestment of root development, making them more susceptible to fracture. Regenerative endodontic procedures induce maturogenesis in necrotic immature permanent teeth in order to promote continuation of root growth. Mineral trioxide aggregate (MTA) is widely used as a blood clot protecting material, although it presents a potential drawback of discoloration. Biodentine is a tricalcium silicate cement with adequate bioactive properties that solve the problem of discoloration. Case report: The current case report demonstrates a maturogenesis of an upper central incisor with chronic apical abscess. Calcium hydroxide was used as intracanal medicament for a week. After a blood clot was formed, Biodentine was placed over it. Periapical healing and root growth were evident at 6 months follow-up. Cone Beam Computed Tomography (CBCT) confirmed apical closure and complete healing at 1 year. Key-learning points: Apical closure of necrotic immature permanent teeth is possible by means of regenerative endodontic procedure. Regenerative endodontic procedure with Biodentine has some advantages over that performed with MTA: No tooth discoloration, hort setting time, asy manipulation. CBCT is the best technique to evaluate root canal growth (length and wide).